Pulmonary arteriovenous malformation as a cause of exercise intolerance in children: a case report - Pierluigi Morreale; Giancarlo Allegro; Mario Giuseppe Vallone; Francesca Finazzo; Vincenzo Antona; Maria Fiorella Sanfilippo; Calogero Comparato; Veronica Notarbartolo (Indonesian Pediatric Society, 2023)
Pulmonary arteriovenous malformations (PAVMs) in children are rare lesions characterized by abnormal low resistance vascular structures connecting a pulmonary artery to a pulmonary vein, resulting in an intrapulmonary right-to-left shunt. The insidious onset and variable signs and symptoms make diagnosis difficult, especially in children. PAVMs can be single or multiple, congenital or acquired, and up to 47-80% of cases are associated with hereditary hemorrhagic telangiectasia (HHT).